2016
DOI: 10.51987/evidencia.v18i4.6366
|View full text |Cite
|
Sign up to set email alerts
|

Actualización de los criterios STOPP-START: una herramienta para la detección de medicación potencialmente inadecuada en ancianos

Abstract: ResumenLa utilización inapropiada de medicamentos en los adultos mayores conlleva frecuentemente la génesis de reacciones adversas debido a los cambios fisiológicos asociados a la edad. Esto aumenta la morbimortalidad determinando un mayor número de admisiones hospitalarias, con incremento de la utilización de recursos sanitarios y gastos en salud. Para poder optimizar la prescripción de medicamentos en los ancianos se han desarrollado en los últimos años herramientas implícitas y explicitas. Los criterios exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 2 publications
0
7
0
1
Order By: Relevance
“…The STOPP/START criteria were developed two decades ago to detect PIPs and improve therapeutic appropriateness in older patients. However, recent studies concluded that the prevalence of PIPs remains high, especially in NH residents [11,35,64].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The STOPP/START criteria were developed two decades ago to detect PIPs and improve therapeutic appropriateness in older patients. However, recent studies concluded that the prevalence of PIPs remains high, especially in NH residents [11,35,64].…”
Section: Discussionmentioning
confidence: 99%
“…PIPs also include: (i) the use of medicines at a higher dose than indicated; (ii) the use of medicines with a high risk of drug-drug or drug-disease interactions; (iii) duplications. Not using clinically indicated beneficial medicines are also considered to be PIPs [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This knowledge base focuses on describing the most common errors in drug prescription. One of their most important features is that these criteria can be integrated into computer systems [ 28 ]. This knowledge base is used at the European level to analyze drugs prescribed to older adult patients.…”
Section: Methodsmentioning
confidence: 99%
“…Existen medicamentos potencialmente inapropiados (MPI) para los adultos mayores por su riesgo significativo de causar una RAM en este grupo etario. Se los considera de esa manera por existir alternativas terapéuticas más seguras, por utilizarse a dosis inapropiadas o por tiempos excesivos, o por interactuar negativamente con otros fármacos o patologías del usuario (3) .…”
Section: Introductionunclassified